Hydrosedimentary Dynamics in the Confluence of the Beni and Mamoré Rivers - Bras Severo, Ednaldo; Ribeiro Marinho, Rogerio; Martinez , Jean-Michel; Pantoja Filizola, Naziano; Llacer Roig, Henrique; Aniceto, Keila; Santini, William; Olivetti, Diogo; Zumak, André; Santos, Osmair; et al. (Revista Brasileira de Geomorfologia, 2026)
This study analyzed hydrosedimentary dynamics at the confluence of the Beni and Mamoré rivers, the two main source rivers of the Madeira River, the largest tributary of the Amazon River. Thirteen field campaigns were conducted between March 2021 and April 2022 at four cross-sections, complemented by historical data from the HYBAM Observatory. The results showed clear contrasts between the tributary rivers: mean suspended sediment concentrations (SSC) were 639 mg.L⁻¹ in the Beni and 218 mg.L⁻¹ in the Mamoré, with specific yields of 2.07 and 0.34 ton.km⁻².yr⁻¹, respectively. The Madeira River exhibited intermediate SSC values (357–371 mg.L⁻¹). During high-water conditions, vertical SSC stratification was more pronounced in the Mamoré and Madeira rivers. The sediment budget indicated a 15% deficit downstream of the confluence, corresponding to the retention of approximately 40 million tons over a 220 km reach. Downstream of this confluence lies the Jirau Hydroelectric Power Plant reservoir, whose dam may influence the study reach. Together, the Beni and Mamoré rivers contribute about 291 million tons of suspended sediment annually to the Madeira River, confirming their strategic role in the Amazon sediment budget and providing a basis for sustainable management of this watershed’s resources.